Public charging requirements for battery electric long-haul trucks in Europe: A trip chain approach - Wasim Shoman; Sonia Yeh; Frances Sprei; Patrick Plötz; Daniel Speth (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
Heavy-duty vehicles (HDV) account for less than 2-5% of the vehicles on the road in Europe but contribute to 15-22% of CO2 emissions from road transport. Battery electric trucks (BETs) could be deployed on a large scale to reduce greenhouse gas emissions but they require charging infrastructure that supports long-haul operations. Therefore, assessing the required charging locations, energy, and power requirements is critical. We use a trip-chain-based model to derive charging requirements for BETs in long-haul operation (defined as travel times over 4.5 hours or distances over 360 km) for Europe in 2030. We convert an origin-destination (OD) matrix into trip chains combined with European truck driving regulations to derive break and rest stops. We show that an average charging area (defined as a 25 x 25 km square, where each square can include multiple charging stations and parking lots with multiple charging points) needs to have four to five times more overnight than megawatt (MW) charging points: We estimate that about 40,000 overnight charging points (50-100 kW, combined charging system, CCS) and about 9,000 megawatt charging system (MCS, 0.7- 1.2 MW) points are required to support a BET share of long-haul operations at 15%. On average, 8 and 2 CCS and MCS chargers are required per charging area, and each CCS and MCS serves, on average, 2 and 11 BETs daily, respectively. The daily electricity demand for public charging of BET in each charging area would be around 110 GWh. The model can be applied to any region with similar data. Future work can consider improving the queuing model, assumptions regarding regional differences of BET penetration and heterogeneity of truck sizes and utilization.
Keywords: 330; Electrification; Heavy duty truck; Charging Station; Battery Electric Truck